Law Enforcement of E-Ticket Cases at the Bantul District Prosecutor's Office - Idhun Fauzan Risalma; Isnawan, Fuadi (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Law enforcement of E-Tilang cases has an important role in maintaining traffic order and security in Indonesia. This study aims to determine the role of the Bantul State Attorney's Office in enforcing the law of e-tickets or electronic tickets for traffic violations and the obstacles to the role of the Bantul State Attorney's Office in enforcing the law of e-tickets or electronic tickets for traffic violations. The research method used in this research is empirical legal research. The approach used in this research is a juridical-empirical approach, namely analysing the legal problems that have been formulated by combining legal materials both primary legal materials, secondary legal materials and tertiary legal materials which are secondary data with primary data obtained in the field through interviews. This research is a new contribution to the understanding of law enforcement related to the E-Ticket case at the Bantul District Attorney's Office. From a series of previous studies, various points of view have been studied in depth. This research aims to provide a more comprehensive understanding of the role and constraints of E-Ticket law enforcement, as well as highlighting innovations and best practices in the context of traffic law enforcement. This research shows that the role of the Bantul State Attorney's Office in enforcing the law of e-tickets for traffic offences is as a protector of personal data, a guarantor of legal certainty and justice, and as an executor. Obstacles in the implementation of its role include the absence of detailed legal rules governing the implementation of electronic-based law enforcement, then in the aspect of resources, still limited technological infrastructure, such as unstable internet access and inadequate computers, in terms of human resources which are still very limited, another inhibiting factor is from the community, the lack of public awareness and understanding of the importance of orderly traffic..